Robot-assisted Neuroendoscopy: Surgeon’s Third Hand – a Proof of Concept Study - Karnam Murali; Rychen Jonathan; Guzman Raphael; Cattin Philippe C.; Rauter Georg; Gerig Nicolas (Current Directions in Biomedical Engineering)
In neuroendoscopy, an assistant surgeon holds the endoscope while the operating surgeon performs brain surgery using surgical instruments in both hands. The assistant surgeon’s task can be strenuous over time, especially in long surgeries, and unsteadiness or tremor might affect the visualization quality that the operating surgeon depends upon. Existing mechanical and pneumatic arms offer limited flexibility. We propose a robotic assistant as a third hand to the surgeon. It holds the endoscope and can be moved freely or held in place. As a proof of concept, we attached a neuroendoscope to an offthe- shelf robot with a custom handle, including a force/torque (F/T) sensor. We qualitatively identified the requirements for the third hand with a surgeon as a participant. We also quantitatively identified the range of forces applied by the endoscope to act as a retractor on two brain phantoms while visualizing the surgical site. With our proof of concept study, we could show the feasibility of robotic assistance in neuroendoscopy. Based on our observations, we found that an intuitive input device to switch the different robot modes, a second F/T sensor to measure the surgeon’s input and tissue interaction separately, and a differently shaped precision grip handle represent promising improvements to our third hand prototype.